Identifikasi Kebutuhan Pengguna Untuk Aplikasi Permainan Edukasi Bagi Anak Usia 4 sampai 6 Tahun - Rosa Delima; Nevi Kurnia Arianti; Brasmati Pramudyawardani (Maranatha University Press, 2015)
User requirement identification is the most important initial phase in developing an eductional game application. At this stage will be formulated characteristics, abilities, and users interest to an application. Targeted users for the game application that will be developed are preschool chidren range from 4 to 6 years. User requirement identification process involves 52 respondents that consists of parents,teachers, and children. Interview, observation, and questionaire are used as a method for data collection. This research produce the characteristics definition of an educational application and basic capabilities for children from 4 to 6 years.Keywords: Educational Game for Children, User Requirement Identification, Children and Computer Game.